Effectiveness of Palestine-Israel Conflict Resolution: Mediation and Humanitarian Assistance by the Indonesian Government 2023-2024 - Prihantoro, Mitro; Hidayana, Dina; Sukrisna, Cecep (International Journal of Science and Society, 2025)
This study aims to analyze the effectiveness of Indonesia's humanitarian diplomacy in the Palestinian-Israeli conflict in the 2023-2024 period, focusing on mediation strategies and the distribution of humanitarian aid. This study uses a descriptive qualitative approach with secondary data analysis sourced from official government documents, reports of international institutions, media publications, and academic literature. The results of the study show that Indonesia consistently plays an active role in humanitarian diplomacy through various international forums such as parliament, the United Nations, the International Court of Justice (ICJ), and the Non-Aligned Movement, by combining diplomatic mediation and moral pressure. Real actions in the form of the delivery of medical aid, logistics, field hospitals, and the readiness of peace forces further strengthen Indonesia's position as an important actor in this field. However, the effectiveness of such diplomacy is still hampered by geopolitical factors, vetoes in the UN Security Council, limited access to Gaza, and challenges in the protection of humanitarian facilities. The research recommendations emphasize the need to strengthen cross-sectoral coordination, more intensive global advocacy, international legal protection for humanitarian assets, and public diplomacy to rally global support. These findings contribute to the understanding of the role of humanitarian diplomacy in international conflict resolution and strategies to improve its effectiveness in the future.